The Influence of Perceptions, Interests, Motivations and Labor Market Considerations on Careers in Taxation on Accounting Students at Buddhi Dharma University) - Alan Renata Pratama; Peng Wi (Global Accounting, 2022)
Study, interests, motivations and labor market considerations affect a career in taxation for Accounting Students at Buddhi Dharma University. The independent variables used in this study were perceptions, interests, motivations and labor market considerations towards a career in taxation, while the dependent variable in this study was a career in taxation. The sample is 117 respondents of Accounting Students at Buddhi Dharma University. The data analysis technique used in this research is multiple linear regression test. The data is processed using SPSS 24. The results of the analysis show that perceptions affect a career in taxation with a t-count value of 2.347 and a significance value of 0.21. Interest has an effect on a career in taxation with a t-count value of 2.869 and a significance value of 0.05. Motivation has an effect on a career in taxation with a t value of 3.205 and a significance value of 0.02. Labor market considerations affect a career in taxation with a t-count value of 2.364 and a significance value of 0.20.